First high resolution analysis of the 3ν2 and 3ν2−ν2 bands of 32S16O2. (November 2017) - Ulenikov, O.N.; Bekhtereva, E.S.; Gromova, O.V.; Berezkin, K.B.; Horneman, V.-M.; Sydow, C.; Maul, C.; Bauerecker, S.
Highlights: High resolution analysis of S16O2 FTIR spectra. Hot transitions. Determination of spectroscopic parameters. Abstract: The second bending overtone band 3 ν 2 of sulfur dioxide has been studied for the first time with high resolution rotation-vibration spectroscopy. The 1530 transitions involving 728 upper state energy levels with J max . = 53 and K a m a x . = 15 have been assigned to the 3 ν 2 band. The 746 transitions belonging to the 3 ν 2 − ν 2 "hot" band have been also assigned in the region of 950–1100 cm − 1 . For the analysis of the assigned transitions, an effective Hamiltonian of an isolated (030) vibrational state (the Watson operator in A -reduction and I r representation) was used. Set of 9 varied parameters was determined which reproduce the initial experimental data with the d rms deviations of 9.0 × 10 − 4 cm − 1 and 9.8 × 10 − 4 cm − 1 for the 3 ν 2 and 3 ν 2 − ν 2 bands, which are comparable with the experimental uncertainties.